Diagnosis and management of pediatric cerebrospinal fluid leakage secondary to inner ear malformations: A report of 13 cases. (August 2020) - Deng, Wenmin; Liu, Jie; Pang, Feng; Zhang, Xiangmin
Abstract: Objectives: Inner ear malformations (IEM) with cerebrospinal fluid (CSF) leakage in children is a rare condition, nevertheless, it may lead to meningitis. Early diagnosis and treatment are crucial. The aims of the study were to summarize the clinical characteristic of pediatric CSF leakage secondary to IEM, and to recommend transcanal endoscopic ear surgery (TEES) as an effective surgical technique for the treatment of CSF leakage with IEM in children. Methods: This was a retrospective study. Thirteen children and fourteen ear surgery were included. Demographics, detail history, laboratory data, Audio test, and imageological examination results were recorded. All the pediatric patients underwent TEES. Results: Most (92.31%) of the children presented with a history of rhinorrhea. 69.23% (9/13) of the children had suffered from meningitis, and the other had presented with respiratory tract infections. The follow-up duration ranged from 0.75 years to 5.29 years. Transcanal endoscopic repair of CSF leakage secondary to IEM was the first surgery with a success rate of 92.86% (13 out of 14 cases). A fistula could be found in the stapes footplate in all pediatric patients. Conclusion: Even if there has been no history of meningitis, the diagnosis of CSF leakage in children suffering from unilateral rhinorrhea and recurrent respiratory tract infection is considered. Auditory brainstem response (ABR) and Temporal bone computed tomography (CT) examinations are suggested to identify IEM. The TEES procedure is recommended in our study as the first choice that repairs CSF leakage secondary to IEM.